AUDIT MANAJEMEN SEBAGAI ALAT UNTUK MENILAI EFISIENSI DAN EFEKTIVITAS PENJUALAN JASA - Ardiana, Tri Tika; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purposes which are going to be achieved by this research are: (1) to assess the implementation ofmanagement audit as an effort to improve the efficiency and the effectiveness in conducting someimprovements on the management activity of CV Royal Makmur Sentosa Surabaya. (2) To analyze, tofind out and to comprehend the human resources audit in improving the efficiency and theeffectiveness level on the services of CV Royal Makmur Sentosa Surabaya. It can be concluded fromthe result of the research that the services in CV Royal Makmur Sentosa Surabaya has run well, yetthe information of the procedure of the recruitment of the employees should be widened and thecompany should cooperate with potential institutions in providing workforces. The employeesassessment system should not be considered from the disciplinary of the attendance only butperformance assessment card should be added and provide routine monitoring on the employees oftheir service activities so the employees can perform maximally in providing services in the company.Keywords: Management Audit, Service, Effectiveness and Efficiency.